Validation of the Geiger-Muller counter model of BDMG-04-02 using the Monte-Carlo technique - Fylonych, Yu.; Zaporozhan, V.; Balashevskyi, O. (Вопросы атомной науки и техники, 2021)
The model of the Geiger-Muller counter as the internal part of BDMG-04-02 detection unit in the calibration fa- cility UPGD-2 was developedin MCNP6.2. The different methods are used for the determination of the Geiger-Muller counter response. The F1 and F8 tally applicability is briefly described. BDMG-04-02 model was validated by comparative analysis of the calculated results and experimental values of the counter responses that obtained on the UPGD-2 calibration facility. Additionally, the absolute, geometric and intrinsic registration efficiency of BDMG-04-02 was determined. The paper has been emphasized the disadvantages of using the method of direct counting of the electrons on the surface of the Geiger-Muller counter (F1). За допомогою методу Монте-Карло, реалізованого в MCNP6.2, розроблено модель лічильника Гейгера-Мюллера БДМГ-04-02 у калібрувальній установці УПГД-2. Стисло описані функціонали F1 та F8 програмного засобу MCNP6.2, що використовуються для визначення відгуку лічильника Гейгера-Мюллера. Валідація моделі БДМГ-04-02 реалізована шляхом порівняльного аналізу розрахункових значень відгуків лічильників з експериментальними, отриманими в калібрувальній установці УПГД-2. Додатково визначено абсолютну, геометричну та внутрішню ефективності реєстрації БДМГ-04-02. Зазначено недоліки використання методу прямої лічби кількості електронів на поверхні лічильника Гейгера-Мюллера (F1). С помощью метода Монте-Карло, реализованного в MCNP6.2, разработана модель счетчика Гейгера-Мюллера БДМГ-04-02 в калибровочной установке УПГД-2. Кратко описаны функционалы F1 и F8 программного средства MCNP6.2, используемые для определения отклика счетчика Гейгера-Мюллера. Валидация модели БДМГ-04-02 реализована путем сравнительного анализа расчетных значений откликов счетчиков с экспериментальными, полученными в калибровочной установке УПГД-2. Дополнительно были определены абсолютная, геометрическая и внутренняя эффективности регистрации БДМГ-04-02. Указаны недостатки использования метода прямого подсчета количества электронов на поверхности счетчика Гейгера-Мюллера (F1).